2021 11th International Conference on Cloud Computing, Data Science &Amp; Engineering (Confluence) 2021
DOI: 10.1109/confluence51648.2021.9377094
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Comparison of COVID-19 Infections Based Upon the Food Habits/Diets in Countries Using RStudio

Abstract: On December 2019, the COVID-19 deadly virus emerged and affected a large population in the world which led to the increase in the death rate of infected patients. Changes in dietary habits and way of living leading from the implementation of lockdown during this pandemic had been detrimental on the nutritional health of individuals. A statistical study was conducted to determine the effect of COVID-19 lockdown on dietary habits, food consumption, and weight in different countries. The primary aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…According to comparison they found that in the countries where lockdown was imposed the obesity was increased and this may be decreased once the lockdown was lifted. The country where people have consumed high energy and protein intakes were the one's that were having least number of cases [2].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…According to comparison they found that in the countries where lockdown was imposed the obesity was increased and this may be decreased once the lockdown was lifted. The country where people have consumed high energy and protein intakes were the one's that were having least number of cases [2].…”
Section: Related Workmentioning
confidence: 99%
“…Step-2: Calculate Euclidean distance of K neighbors. The formula is given by equation ( 1) √(𝑥 2 − 𝑥 1 ) 2 + (𝑦 2 − 𝑦 1 ) 2 (1) Where (x1,y1) and (x2, y2) are the points of 2 neighbors.…”
Section: Knn(k-nearest Neighbor)mentioning
confidence: 99%
“…Also, Ramachandran et. al., [11] have analyzed the effect of food habits on COVID-19 infections and recovery.…”
Section: A Acquired Immunitymentioning
confidence: 99%
“…The paper could be improved by studying relations between more countries to arrive at a more concrete conclusion. As there will be variation based on diet and satiety of people in the attempt to achieve immunity and countries under lockdown have shown food supply at lower rate than minor lockdown [17].…”
mentioning
confidence: 99%